Transcriptional profiles of genes related to electrophysiological function in Scn5a+/− murine hearts. Issue 19 (7th October 2021) - Takla, Michael; Edling, Charlotte E.; Zhang, Kevin; Saadeh, Khalil; Tse, Gary; Salvage, Samantha C.; Huang, Christopher L.‐H.; Jeevaratnam, Kamalan
Abstract: The Scn5a gene encodes the major pore‐forming Nav 1.5 (α) subunit, of the voltage‐gated Na + channel in cardiomyocytes. The key role of Nav 1.5 in action potential initiation and propagation in both atria and ventricles predisposes organisms lacking Scn5a or carrying Scn5a mutations to cardiac arrhythmogenesis. Loss‐of‐function Nav 1.5 genetic abnormalities account for many cases of the human arrhythmic disorder Brugada syndrome (BrS) and related conduction disorders. A murine model with a heterozygous Scn5a deletion recapitulates many electrophysiological phenotypes of BrS. This study examines the relationships between its Scn5a +/− genotype, resulting transcriptional changes, and the consequent phenotypic presentations of BrS. Of 62 selected protein‐coding genes related to cardiomyocyte electrophysiological or homeostatic function, concentrations of mRNA transcribed from 15 differed significantly from wild type (WT). Despite halving apparent ventricular Scn5a transcription heterozygous deletion did not significantly downregulate its atrial expression, raising possibilities of atria‐specific feedback mechanisms. Most of the remaining 14 genes whose expression differed significantly between WT and Scn5a +/− animals involved Ca 2+ homeostasis specifically in atrial tissue, with no overlap with any ventricular changes. All statistically significant changes in expression were upregulations in the atria and downregulations in the ventricles. This investigation demonstrates the value of future experiments exploring for and clarifying links between transcriptional control of Scn5a and of genes whose protein products coordinate Ca 2+ regulation and examining their possible roles in BrS. Abstract : Volcano plot of differentially expressed pre‐selected genes, contrasting transcription in ventricular Scn5a +/− to wild type. The y ‐axis indicates unadjusted p values based on Student's t ‐tests, while the x ‐axis indicates the log2 of each normalized fold change.